Bioaccumulation of heavy metals by endemic Viola species from the soil in the vicinity of the As-Sb-Tl mine "allchar' Republic of Macedonia - Baceva, K; Stafilov, T; Matevski, V (My University, 2014)
Allchar mine is an abandoned arsenic-antimony-thallium deposit located on the northwestern part of Kozuf Mt., Republic of Macedonia. Allchar is a unique deposit within the world, due to the variety of its mineral composition especially and in the high content of thallium. The aim of this work was to assess the level of contamination at this post-mining area as well as to determine the intensity of accumulation of various elements (Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, Ga, K, Li, Mg, Mn, Mo, Na, Ni, P, Pb, Rb, S, Sb, Sr, Tl, V, and Zn) with focus on As, Sb and Tl, in two endemic Viola species from this locality (Viola allcharensis G. Beck, Viola arsenica G. Beck) and one Balkan endemic species (Viola macedonica Boiss. & Heldr.). Samples of different plant parts and soil were digested and then analysed by ICP-AES. It was found that the accumulation of As, Sb, and Tl in these endemic species is significantly high. In this study a systematic investigation of the As-Sb-Tl contamination of soils and their bioavailability was carried out using the extraction procedure in order to explore the mobility and potential bioavailability of the As, Sb, and Tl.